5t-0=-3t+7

Simple and best practice solution for 5t-0=-3t+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t-0=-3t+7 equation:


Simplifying
5t + 0 = -3t + 7

Reorder the terms:
0 + 5t = -3t + 7
Remove the zero:
5t = -3t + 7

Reorder the terms:
5t = 7 + -3t

Solving
5t = 7 + -3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '3t' to each side of the equation.
5t + 3t = 7 + -3t + 3t

Combine like terms: 5t + 3t = 8t
8t = 7 + -3t + 3t

Combine like terms: -3t + 3t = 0
8t = 7 + 0
8t = 7

Divide each side by '8'.
t = 0.875

Simplifying
t = 0.875

You can always share this solution

See similar equations:

| 3(-14+2)=4(5-14) | | -5(n+8)=-98 | | 4g+3g+9g= | | x^2-13x=-30 | | 4(3x-2)=52 | | 5x^2-24x+18=0 | | 3x^2-6x+45=0 | | x^2-13=-30 | | 32+5(8.6)=n | | 5r+r+4r= | | 24=5x+6-2x | | 11r-6r+5r=168 | | 32+5(8.6)= | | 3(-14+2)=4(5-13) | | 3y+10=9 | | 3m-4=2m-13 | | 41+8z=-z^2 | | 8x+12=100 | | b-3+3b=36 | | 3y+7=9 | | 4(y+2)=5(y-5) | | 6x-10=-18x-4 | | 3x^2-15x+45=0 | | 2(-2+x)-1(x-4)=0 | | (x-6)(5x+3)=0 | | 27=y | | (x+3)(6x+7)=0 | | 2y-8=-y+4 | | 6x^2-8x+3=0 | | 0=-5h-2h | | 4h*6h= | | -2+2y=-4 | | 3-4r=10r+10 | | (3m-4n-7)-(8m+n-6)= | | 32+5n=75 | | 2y=4x-3 | | 2+11x=12x-6 | | (3m-4n-7)(8m+n-6)= | | y^2-16x-6y+25=0 | | 3(a-2)=9(a+2) | | 9x-15= | | 3=12-3x | | -7h-4=h+4 | | 62-c=42 | | -3b-2a-4c+5b-8a= | | 4d-8=19 | | 4(x-4)-11x= | | 6c-12=48 | | 25h=20h+15 | | 1-2x=16-5x | | 4y+6=-14 | | 9(6x+3)= | | 7x=11x+16 | | 3x+-7=-8 | | 9a-4a+a-10= | | 6w+5=w-35 | | 3(2t^2-5)=t | | -5x+-5=9x | | a^2x^2-8abx+16b^2=0 | | 97-4x=41x+17 | | 9=a(14) | | 11-10x=40-17x | | 10x+35=28x+35 | | -74-9x=7x+22 | | 8p-24+10p=138 |

Equations solver categories